Morbid obesity is associated with mortality and acute kidney injury in hospitalized patients with COVID-19. (October 2021) - Martín-del-Campo, Fabiola; Ruvalcaba-Contreras, Neri; Velázquez-Vidaurri, Alma L.; Cueto-Manzano, Alfonso M.; Rojas-Campos, Enrique; Cortés-Sanabria, Laura; Espinel-Bermúdez, María C.; Hernández-González, Sandra O.; Nava-Zavala, Arnulfo H.; Fuentes-Orozco, Clotilde; Balderas-Peña, Luz; González-Ojeda, Alejandro; et al.
Summary: Background & aims: Mexico has one of the highest mortality rates by COVID-19 worldwide. This may be partially explained by the high prevalence of overweight/obesity found in general population; however, there is limited information in this regard. Furthermore, acute kidney injury (AKI) and need for renal replacement therapy (RRT) associated to obesity in patients with COVID-19 are still topics of discussion. Aim : To explore the association of obesity, particularly morbid obesity, with mortality and kidney outcomes in a Mexican population of hospitalized patients with COVID-19. Methods: Retrospective cohort study of 773 patients with COVID-19 hospitalized in a tertiary-care teaching hospital in the Mexican state of Jalisco. Baseline body mass index was classified as: normal weight (18.5–24.9 kg/m 2 ), overweight (25–29.9 kg/m 2 ), obesity (30–39.9 kg/m 2 ), and morbid obesity (≥40 kg/m 2 ). AKI was diagnosed according to KDIGO clinical practice guidelines. Results: At baseline, 35% of patients had overweight, 39% obesity and 8% morbid obesity. Patients with obesity were younger, more frequently women and with hypertension than normal weight and overweight patients. Frequency of complications in the univariate analysis were not significantly associated to obesity, however in the multivariate analysis (after adjusting for baseline clinical and biochemical differences), morbid obesity was significantly associated to an increased risk of AKI [OR = 2.70 (1.01–7.26), p = 0.05], RRT [OR = 14.4 (1.46–42), p = 0.02], and mortality [OR = 3.54 (1.46–8.55), p = 0.005]. Conclusions: Almost half of the sample had obesity and morbid obesity. Morbid obesity was significantly associated to an increased risk of AKI, RRT and mortality in hospitalized patients with COVID-19.